HUBUNGAN AHKLAK TASAWUF (MORAL ETHIC) DALAM LAW AND SOCIAL CHANGES DI INDONESIA - Istiqomah, Uji; Tarlam, Alam (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2023)
Humans have a powerful nature that can do and will according to his wishes. If this desire and will is not limited, then humans can also become a threat to other humans. So that the law was created, one of which is to limit the space for human movement so that they do not act according to their own will. One of the functions of law is to create a society that is safe, peaceful and just. Regardless of whether the change brings benefit or harm, it is clear that the dynamics of human life as social beings certainly experience ups and downs. Keywords: Relationship, Tasawwuf Morals, Law And Social Changes.